Information assurance and computer security - Thomas, Johnson P. (IOS Press, 2013)
Today's society can no longer function without information technology. Essential infrastructure including the transportation system, banking, the entertainment industry, the healthcare system, government, the military and the education system can no longer survive without modern technology. This increasing dependence on information technology creates new opportunities for the benefit of society. However, it also opens an avenue that can be exploited for illicit purposes. The stakes are high and many attacks go undetected or unreported. In addition to losses such as data or other forms of intel.